Research on DHT Simulation and Torque Distribution Strategy of Dual Motors with Two Speed - Zhang Zhigang; Wang Xiaosong; Qing Hai; Zhang Daiming (Jixie chuandong)
Dedicated hybrid transmission (DHT) has attracted wide attention because of its light weight and small overall size. The hybrid system has a variety of different power sources, which can change the operation mode to respond to different operating conditions, thus improving the fuel economy. The DHT torque distribution control strategy model is built on Matlab/Simulink platform to control the optimal output torque of the engine, so as to ensure the engine operating in the economic zone. Off-line simulation is carried out based on the test cycle conditions of light passenger vehicles in China and light vehicle in the world. The results show that the matching accuracy of the expected speed and the actual speed is high, and the simulation model is accurate and reliable. Under CLTC_P condition, the fuel consumption of 100 km is 5.74 L, saving 36.33% than that of traditional fuel vehicles.